Digital Participation and Active Involvement of Civil Society in Organizing Ideal Elections - Farhan Fathur Rahman (ISNU Sumatera Utara, 2024)
Digital participation and active involvement of civil society are important elements in organizing ideal and democratic elections. Digital technology opens up new spaces for the public to participate in the election process, either through social media, digital platforms, or special applications designed to monitor and ensure transparency and accountability of elections. The research method used is normative juridical, with a legislative, conceptual, and comparative approach. The legislative approach is used to examine regulations and policies related to digital participation in elections, while the conceptual approach is used to understand the concept of digital participation and the role of civil society. The comparative approach is used to compare digital participation practices in elections in various countries, in order to gain a broader understanding of the effectiveness of the strategies implemented. The results of the discussion show that digital participation has great potential in increasing civil society involvement, but there are still significant challenges, such as low digital literacy, the risk of spreading misinformation, and limited access to technology. Clear and systematic regulations are needed to support digital participation effectively and prevent misuse that can damage the integrity of elections. In conclusion, digital participation is an important means to increase public involvement in organizing ideal elections, but it needs to be accompanied by supportive policies and adequate public education. The suggestion from this research is to strengthen regulations on the use of technology in elections, increase public digital literacy, and encourage innovation in safe and transparent digital platforms for election participation.